PERSEPSI MAHASISWA TERHADAP APLIKASI “KORE WA NANI” SEBAGAI MEDIA PEMBELAJARAN MEMBACA KANJI II - Ahmad Kurniawan; Frida Philiyanti; Yuniarsih (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2026)
Learning kanji in Japanese is often a major challenge for learners, primarily due to visual complexity, the large number of characters, and differences in reading methods (onyomi and kunyomi). The advent of smartphone applications has revolutionized language learning, offering innovative solutions to address these challenges. The "Kore wa Nani" application, featuring a widget for quick access to kanji reading exercises based on the Basic Kanji Book Vol. II, represents one such tool tailored for learners. This study aims to analyze students' perceptions of the "Kore wa Nani" application as a learning medium for reading kanji in the Kanji II course at the Japanese Language Education Program, Universitas Negeri Jakarta. The research employs a descriptive qualitative approach with data collected through closed and open-ended questionnaires, analyzed based on four dimensions of the Mobile Apps Rating Scale (MARS): Engagement, Functionality, Aesthetics, and Information Quality. The findings indicate that students have a positive perception of the application, particularly regarding its ease of use (Functionality) and visual appeal (Aesthetics). The widget feature is considered to facilitate access and enhance learning motivation, despite technical issues such as lag on older devices and the need for more varied content. The application is deemed effective in supporting independent learning and helping students memorize kanji readings (onyomi and kunyomi) in sentence contexts. However, it is not entirely perceived as more engaging than traditional methods like textbooks. This study provides recommendations for developers to improve technical performance and content variety.